Defining general practitioner and population catchments for spatial equity studies using patient enrolment data in Waikato, New Zealand. (February 2020) - Whitehead, Jesse; Pearson, Amber L.; Lawrenson, Ross; Atatoa-Carr, Polly
Abstract: The enhanced-two-step-floating-catchment-area (E2SFCA) method is a popular measure of the spatial accessibility of healthcare such as general practitioner (GP) services. However, the key step of defining appropriate GP and population catchment sizes is often overlooked. Applications of E2SFCA methods use a range of catchment sizes, most of which are arbitrarily defined due to a lack of real-world data to inform this decision. The use of inappropriate catchment sizes may under- or over-estimate spatial accessibility in some areas. In this paper patient enrolment data is used to determine appropriate GP and population catchment sizes in the Waikato, central North Island, region of New Zealand. A range of thresholds were tested, including: 100, 95, 90, 85, 75, and 65 percent of enrolled patients. Initial results suggest that catchment sizes vary across rural and urban areas. Further, incorporating variable data-driven population catchments recognises patient travel patterns and appears to improve spatial accessibility results in a mixed urban-rural context, although further modification may be necessary. This study has demonstrated an effective approach to defining appropriate GP and population catchments for use with the E2SFCA method, where access to patient enrolment data is available. Highlights: An approach to defining catchment sizes using enrolment records is proposed. Catchment sizes vary with rurality and differ from 'default' catchment sizes. A case study illustrates the impact on accessibility in a mixed urban-rural context. Data-defined catchments may improve FCA spatial accessibility results. Service-defined and population-defined catchments affect results differently.